Knowledge attitude practice on breast self-examination in a rural area in North Kerala - Ishaaque, Sherin; Gopalamenon, Nandini (International Journal Of Community Medicine And Public Health, 2019)
Background: Breast cancer is the most common cancer in women. It is estimated that 5,08,000 women died due to breast cancer in 2011 globally. Late detection of breast cancer decreased the survival rate to 56% and the 5-year survival rate reached 85% with early detection of breast cancer. Breast self-examination (BSE) is an inexpensive tool which helps women to detect any early changes in their breasts and thus helps to reduce the breast cancer mortality and morbidity. The present study was designed to determine the knowledge, attitude and practice regarding BSE among women aged 25 years and above. Methods: A community-based, cross-sectional study was conducted in rural North Kerala, among 206 women aged ≥25 years selected by cluster sampling. Data was collected using a semi-structured questionnaire. Results: The participants were aged between 25-94 years (mean age 40.15±13.17). 62.6% have heard about BSE. Among the 206 participants, 12% had good knowledge while 10.6% knew the correct technique of doing BSE and only 0.06% knew that BSE must be performed once a month. Though 80.5% have good attitude regarding BSE, only 36% practised BSE and only 0.04% performed it every month. Educational status (high school and below vs higher secondary and above) was found to be significantly associated with knowledge (p<0.001) and practice (p=0.003). Knowledge regarding BSE was significantly associated with practice (p<0.001) while family history of breast cancer was not (p=0.072). Conclusions: The respondents had good attitude regarding BSE but knowledge and practice on BSE were very poor. Educational status has an influence on the knowledge and practice while family history did not have any influence.